Teacher Preparation Programs: A Comparative Study between the Kingdom of Saudi Arabia and Singapore, Japan and South Korea - Alenazi, Abdulaziz Matar Olyan (Journal of Educational and Psychological Sciences, 2020)
The present study is based on comparing teacher training programs in Saudi Arabia with teacher training programs in Singapore, Japan and South Korea, in order to find out the reality of these programs and detect similarities and differences among them and the study used the method of comparative analysis, and the tool was represented in a comparison card, which included the following aspects (the authorities supervising the teacher preparation programs - the duration and the system of teacher preparation - the criteria for accepting students - aspects of the teacher preparation program - the evaluation and testing system). One of the most important results of the study was the agreement of the Kingdom of Saudi Arabia and all the comparative countries that the Ministry of Education is responsible for teacher training programs. The study also showed that scientific research is part of the components of teacher training programs in the Kingdom of Saudi Arabia and Singapore. Based on the results, the researcher made a set of recommendations, the most important is: Benefiting from teacher training programs in South Korea by dividing the period of practical training into teaching assistance, teaching practice, school administration, and educational volunteer programs.
Keywords: comparative study; development of teacher preparation programs; Saudi Arabia; Singapore; Japan; South Korea